PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER) DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Luluk Innafisah; Afifudin Afifudin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted with the aim of analyzing the effect of earnings per share, price earnings ratio, and dividend payout ratio on the value of the company and providing benefits, namely: for issuers, can be used as consideration in the framework of policy making related to the company's financial performance in the future come. For investors, the results of this study are expected to provide positive input and consideration when making an investment so that they can choose the most appropriate investment decisions. For academics, this research can be used as reference material in subsequent studies as well as a means to add insight. The data used in this research is secondary data. The population used in this study were all property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The sample selection uses purposive sampling. Based on these criteria, obtained 35 sample companies in this study were then analyzed using the regression data panel. The results showed that earnings per share, price earnings ratio, and dividend payout ratio had a positive effect on firm value.                                                                                                                          Keyword: earning per share, price earning ratio, devidend payout ratio, and company’s value.